FACTORS RELATED TO EVENTS OF LOW BIRTH WEIGHT (LBW) IN PERINATAL ROOM RSHD BENGKULU CITY - Helleri Fivtrawati (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2022)
Low birth weight babies (LBW) continue to be a global public health problem. Basically babies with birth weight less than 2500 grams have a greater risk of health problems due to many factors including factors from the mother, from the baby and from the environment. to determine the factors associated with the incidence of low birth weight (LBW) in the perinatal room RSHD Bengkulu City. This type of research is an analytical study with a case control approach. The population is all newborns in RSHD Bengkulu City during January - December 2019. The sample in this study is mothers who have LBW babies taken using total sampling technique, namely mothers who have LBW babies with The incidence of 50 babies and as a control was taken as many as 50 respondents at RSHD Bengkulu City in 2019 using the 1: 1 comparison method so that the total sample taken was 100 cases. The sampling technique used was systematic random sampling. Data were analyzed using univariate and bivariate analysis using chi-square at the 95% confidence level (p <0.05). The results obtained: Out of 100 babies, there are 50 babies (50.0%) babies who have low birth weight (LBW) and not babies who do not experience low birth weight (LBW), 62 babies (62%) mothers have preeclampsia, 70 mothers (70.0%) experienced pregnancy anemia, 57 mothers (57.0%) with multiparous / grandemultipara parity, there was no relationship between preeclampsia and the incidence of low birth weight (LBW) in the perinatal room RSHD Bengkulu City, there was a relationship between anemia and parity with the incidence of low birth weight (LBW) in the perinatal room RSHD Bengkulu City.